2022
DOI: 10.3389/fnins.2022.813472
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Reduces Neuroinflammation Through Microglia Polarization Regulation to Improve Functional Recovery After Spinal Cord Injury

Abstract: BackgroundSpinal cord injury (SCI) is a devastating disease that lacks effective treatment. Interestingly, recent studies indicated that vagus nerve stimulation (VNS), neuromodulation that is widely used in a variety of central nervous system (CNS) diseases, improved motor function recovery after SCI. But the exact underlying mechanism of how VNS ameliorates SCI is unclear. This study aimed to confirm the efficacy and further explore the potential therapeutic mechanism of VNS in SCI.MethodA T10 spinal cord com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
14
0
2
Order By: Relevance
“…Importantly, vagus nerve stimulation does not appear to exacerbate autonomic dysreflexia events, alluding to its safety as a possible therapeutic to improve autonomic function after SCI (Sachdeva et al, 2020). Interestingly, vagus nerve stimulation in a rodent SCI model reduces neuroinflammation, i.e., expression of pro-inflammatory cytokines while also increasing the expression of anti-inflammatory cytokines, after SCI (Chen et al, 2022), suggesting that vagus nerve stimulation has broad effects and any recovery may be through multiple mechanisms.…”
Section: Considerations For the Futurementioning
confidence: 99%
“…Importantly, vagus nerve stimulation does not appear to exacerbate autonomic dysreflexia events, alluding to its safety as a possible therapeutic to improve autonomic function after SCI (Sachdeva et al, 2020). Interestingly, vagus nerve stimulation in a rodent SCI model reduces neuroinflammation, i.e., expression of pro-inflammatory cytokines while also increasing the expression of anti-inflammatory cytokines, after SCI (Chen et al, 2022), suggesting that vagus nerve stimulation has broad effects and any recovery may be through multiple mechanisms.…”
Section: Considerations For the Futurementioning
confidence: 99%
“…Although clinical studies assessing the efficacy of VNS in SCI patients is limited, pre-clinical studies highlight possible mechanisms and provide promising results. VNS was shown to alleviate neuroinflammation after SCI through promoting the shift of pro-inflammatory M1-polarized microglia to anti-inflammatory M2 phenotype via upregulation of alpha 7 nicotinic acetylcholine receptors ( 113 ). Specifically, VNS inhibited pro-inflammatory factors such as Tumor Necrosis Factor (TNF)-α, Interleukin (IL)-1β, IL-6 and increased expression of anti-inflammatory factor IL-10.…”
Section: Modalitiesmentioning
confidence: 99%
“…Interestingly, individuals with SCI have reduced vagal tone, suggesting vagal nerve stimulation could be beneficial in this population. Indeed, Chen et al, used electrical vagal nerve stimulation in spinally injured rats and found that it improved functional recovery, reduced tissue damage, and reduced the release of pro-inflammatory cytokines (TNFα, IL1 β, and IL6) and increased levels of anti-inflammatory cytokine IL10 ( 175 ), however pain was not assessed.…”
Section: Non-pharmacological Treatments For Sci Painmentioning
confidence: 99%